Development of a circulating miRNA assay to monitor tumor burden: From mouse to man. Issue 2 (28th October 2015) - Greystoke, Alastair; Ayub, Mahmood; Rothwell, Dominic G.; Morris, Dan; Burt, Deborah; Hodgkinson, Cassandra L.; Morrow, Christopher J.; Smith, Nigel; Aung, Kyaw; Valle, Juan; Carter, Louise; Blackhall, Fiona; et al.
Abstract : Circulating miRNA stability suggests potential utility of miRNA based biomarkers to monitor tumor burden and/or progression, particularly in cancer types where serial biopsy is impractical. Assessment of miRNA specificity and sensitivity is challenging within the clinical setting. To address this, circulating miRNAs were examined in mice bearing human SCLC tumor xenografts and SCLC patient derived circulating tumor cell explant models (CDX). We identified 49 miRNAs using human TaqMan Low Density Arrays readily detectable in 10 μl tail vein plasma from mice carrying H526 SCLC xenografts that were low or undetectable in non‐tumor bearing controls. Circulating miR‐95 measured serially in mice bearing CDX was detected with tumor volumes as low as 10 mm3 and faithfully reported subsequent tumor growth. Having established assay sensitivity in mouse models, we identified 26 miRNAs that were elevated in a stage dependent manner in a pilot study of plasma from SCLC patients (n = 16) compared to healthy controls (n = 11) that were also elevated in the mouse models. We selected a smaller panel of 10 previously reported miRNAs (miRs 95, 141, 200a, 200b, 200c, 210, 335#, 375, 429) that were consistently elevated in SCLC, some of which are reported to be elevated in other cancer types. Using a multiplex qPCR assay, elevated levels of miRNAs across the panel were also observed in a further 66 patients with non‐small cell lung, colorectal or pancreatic cancers. The utility of this circulating miRNA panel as an early warning of tumor progression across several tumor types merits further evaluation in larger studies. Highlights: Simple miRNA assay developed suitable for plasma volumes as low as 10 μl. Assay suitable for serial weekly monitoring of human xenograft growth in mice. Can detect xenograft tumor volumes as low as 10 mm3 and correlates with tumor growth. Selected miRNAs elevated in SCLC, NSCLC, colorectal and pancreatic cancers.